Tracking the nematicity in cuprate superconductors: a resistivity study under uniaxial pressure. (17th August 2022) - Xie, Tao; Liu, Zhaoyu; Gu, Yanhong; Gong, Dongliang; Mao, Huican; Liu, Jing; Hu, Cheng; Ma, Xiaoyan; Yao, Yuan; Zhao, Lin; Zhou, Xingjiang; Schneeloch, John; et al.
Abstract: Overshadowing the superconducting dome in hole-doped cuprates, the pseudogap state is still one of the mysteries that no consensus can be achieved. It has been suggested that the rotational symmetry is broken in this state and may result in a nematic phase transition, whose temperature seems to coincide with the onset temperature of the pseudogap state T ∗ around optimal doping level, raising the question whether the pseudogap results from the establishment of the nematic order. Here we report results of resistivity measurements under uniaxial pressure on several hole-doped cuprates, where the normalized slope of the elastoresistivity ζ can be obtained as illustrated in iron-based superconductors. The temperature dependence of ζ along particular lattice axis exhibits kink feature at T k and shows Curie–Weiss-like behavior above it, which may suggest a spontaneous nematic transition. While T k seems to be the same as T ∗ around the optimal doping and in the overdoped region, they become very different in underdoped La 2 − x Sr x CuO4 . Our results suggest that the nematic order, if indeed existing, is an electronic phase within the pseudogap state.